Modification of bi-composite membrane support layer by macro puncture for membrane distillation application - Jeong, Seongpil; Lee, Kangho; Kim, Hong-Seok; Lee, Seockheon (ELSEVIER SCIENCE BV, 2016)
Membrane distillation (MD) is a thermally driven membrane process. For MD application, a hydrophobic and porous membrane is required. A bi-composite membrane has been introduced for many MD applications because of its superior membrane performance, especially flux. In this research, in order to increase the flux of a commercial bi-composite membrane, various macro punctures were formed in the support layer. The modified MD membranes were tested in a direct contact membrane distillation (DCMD) configuration. The flux of a modified membrane was affected by the size and location of macro punctures and overall porosity in the support layer. The flux of a modified membrane was enhanced up to 27% compared with that of pristine membrane when the size of the macro puncture and overall porosity of the support layer were larger than 20 mm(2) and 60%, respectively. The overall porosity and size and location of macro punctures in the support layer affected the flux due to the turbulent production in the permeate side. The membrane integrity was checked not only by the tensile strength of the modified membrane samples but also by the long term operation by using the secondary effluent of the waste-water treatment plant as a feed. (C) 2015 Published by Elsevier B.V.
Keywords: COMMERCIAL PTFE MEMBRANES; THIN-FILM-COMPOSITE; OSMOSIS MEMBRANES; RECENT PROGRESS; DESALINATION; PERFORMANCE; MICROSTRUCTURE; HYDROPHOBICITY; SOLAR; WATER